Research on the Relationship Between Service Guarantee Perception and Customer Value in the Chinese Context - Yu, Huang-he; Zhao, Shu-kuan; Hsu, Mao-Chou (Frontiers in Psychology, 2022)
As an excellent management tool, service guarantee can improve the competitive advantage of enterprises and allow consumers to obtain high-quality products and services. However, in the current Chinese context, this tool has not played its proper function. One important reason is the perception deviation of Chinese consumers. This research analyzes the main reasons for this deviation, puts forward related hypotheses and research models, discusses the influence of disposition to trust of contract, perceived structural assurance, and subjective norm on service guarantee perception. Also, this study discusses service guarantee perception of customers through perceived risk and quality. Through the verification of 574 sample data, the main conclusions are as follows: (1) Disposition to trust of contract, subjective norms, and perceived structural assurance significantly affect service guarantee perception positively; (2) Service guarantee perception positively affects customer value; (3) Service guarantee perceptions are obviously different between people of different ages, education levels, and income levels. Hopefully that these conclusions can have the following enlightenment to enterprises serving Chinese consumers: (1) in the designing stage of service guarantee, customers' perception of this guarantee should be a consideration; (2) customer value can be a proper direction if an enterprise wish to lead the customer’s guarantee perception; (3) Not all products need the same level of service guarantee; (4)The proper service guarantee level depends on various statistical characteristics of target customers of the service.